STRATEGI PEMASARAN : UPAYA MENINGKATKAN REPUTASI BANK DAN COSTUMER TRUST PADA TABUNGAN DI BANK SYARIAH INDONESIA - MUFIDATUL HIMMAH; ANIS FITRIA; SOFIATUL WAHIDAH; ATIQURRAHMAN ATIQURRAHMAN (Nurul Jadid University, 2022)
This study discusses the marketing strategy of the savings product Tabungan and how the marketing strategy can have an impact on the level of company reputation and the level of customer trust in BSI Probolinggo . This study aims to (1) understand and find out more about the marketing strategy used by BSI Probolinggo , in maeting its Tabungan savings product. (2) describe the efforts of BSI Probolinggo in marketing its products to continue to maintain the existence of the products they have and overcome the marketing problems they face. (3) to determine the impact of the marketing strategy on the level of reputation and customer trust in the company. Using this type of qualitative research with direct observation and interview methods. From the observations made by the author, the results of the study are as follows: (1) Tabungan savings is a savings product that is most in demand by customers with a percentage of 36.5% of the use of a total of 6 fundraising products offered with 5fivesavings products and 1-time deposit producWorship (2) the use of an effective sales strategy turns out to have an impact on the level of company reputation and the trust given by customers, the more products sold indicate that the public has interest and trust in the product, and automatically increases the reputation of the company (3) the marketing strategy used by the company BSI Probolinggo is still traditional, with direct marketing methods by Customer Service. (4) the lack of use of digital technology in marketing Tabungan savings products. (5) To maintain customer loyalty, usually, BSI Probolinggo gives gifts to customers, shopping discounts and other direct prizes.